The great snake escape - Coxe, Molly (New York : HarperCollins, 1994)
Mirabel, a goose, and her friend, Maxie, a frog, get a scare one day when a king cobra escapes from the zoo.
K-3
1 3 10 11 13 18 26 29
Keywords: Geese -- Fiction; Frogs -- Fiction; Snakes -- Fiction